Commercial Signage In Beachwalk Kuta: A Linguistic Landscape Approach To Tourist Engagement - Safitri, Luh Mega (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2025)
This study aims to examine the linguistic meanings embedded in outdoor commercial signage displayed on banners at various outlets in Beachwalk Shopping Center, Kuta. Employing a qualitative research approach, this study adopts the framework of linguistic landscape analysis to explore how language is used in public commercial spaces. Data was collected through photographic documentation using a smartphone, capturing a variety of banners present in the shopping center. The collected data were then analyzed using Multimodal Discourse Theory proposed by Kress and Van Leeuwen (2006) and Leech’s (1983) Theory of Meaning to identify the underlying linguistic and semiotic elements. The findings reveal that the linguistic expressions found in the commercial banners convey conceptual, connotative, and affective meanings. Furthermore, these banners reflect emotions, aspirations, persuasive strategies, and behavioral representations of business owners or advertisers. The study highlights the role of linguistic landscape in shaping consumer perceptions and its potential implications for tourism and commercial branding in public spaces.